Physical activity in physiotherapy students: Levels of physical activity and perceived benefits and barriers to exercise - Diana Kgokong; Romy Parker (AOSIS, 2020)
Background: Physiotherapists have been identified as key role players in health promotion, prevention and treatment of non-communicable diseases. Objectives: The aim of this study is to describe the perceived benefits and barriers to exercise and their association with levels of physical activity (PA) in physiotherapy students attending university in the Western Cape province of South Africa. Method: This study follows a quantitative, cross-sectional, survey design. Two hundred and ninety-six participants were recruited from three universities in the Western Cape. Participants completed a demographic questionnaire (DQ), Exercise Benefits and Barriers Scale (EBBS) and the International Physical Activity Questionnaire (IPAQ). Results: Female students accounted for 83% of the sample. Out of the 296 participants, 58% lived off-campus and 65% were involved in sporting activities six hours per week. The median score on the EBBS was 136 (54-167) for all years. Responses with the highest agreement for perceived benefits were associated with physical performance. Alternatively, responses with the highest agreement for perceived barriers were associated with physical exertion. Only 37.5% students engaged in high PA. Conclusion: Undergraduate physiotherapy students in the Western Cape across all three universities do not engage in adequate PA. In this group of students, benefits associated with high PA related to physical performance and barriers associated with low levels of PA related to physical exertion. Clinical implications: Physiotherapists who do not practise what they preach are not effective role models and may not be effective in obtaining behaviour change through PA-related health promotion.